Implementasi Literasi Digital Melalui Pelatihan Pembuatan Game Edukasi Berbasis Canva Untuk Anak Usia Dini Di Tk Ra Muslimat Nu - suci salsabila, dara; Arifani, Rania; Apriliani, Anggun; Setiawati, Nursela; Indriani Harianja, Sri; Fikri Rosyadi, Akhmad (Pendidikan Sejarah FKIP Universitas JAMBI, 2025)
This community service activity aimed to implement digital literacy through training in creating Canva-based educational games for early childhood learners at TK RA Muslimat NU. The method used a participatory approach conducted through four stages: preparation, media design, implementation, and evaluation. The activity was carried out directly in the classroom by involving teachers and children aged 5–6 years through digital play activities using Canva-based educational games. The results showed that teachers gained an understanding of how to use and implement Canva-based educational games directly in the classroom without separate training sessions. In addition, the children demonstrated high enthusiasm, actively spelled letters, identified missing and initial letters, and guessed animal sounds. These results indicate that the use of Canva-based educational games supports digital literacy and creates enjoyable, interactive, and meaningful learning experiences for early childhood.